2021
DOI: 10.1093/nutrit/nuab002
|View full text |Cite
|
Sign up to set email alerts
|

Biological activities of açaí (Euterpe oleracea Mart.) and juçara (Euterpe edulis Mart.) intake in humans: an integrative review of clinical trials

Abstract: Açaí (E. oleracea) and juçara (E. edulis) are berries considered a source of bioactive compounds, especially anthocyanins and unsaturated fatty acids, with recognized health-promoting activities. An integrative review was conducted to identify available clinical trials that evaluated the effects of açaí and juçara intake on the human organism. Science Direct and Medline databases were searched. Human studies that evaluated any biological activities after açaí and juçara intake were included in this review. Twe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 69 publications
1
8
0
Order By: Relevance
“…In addition, experiments in rats revealed that a diet supplemented with 2% Açai pulp for six weeks caused a reduction in erythrocyte protein oxidation compared to control animals [ 57 ]. In fact, compared with other antioxidant-rich fruits, Açaì extract has 4.8, 6.1, and 7.5-fold the antioxidant capacity of blackberries, blueberries, and strawberries, respectively [ 23 ]. The antioxidant effect of Açaì extract has been attributed to its phytochemical composition comprising hydroxybenzoic acids and flavanols, along with cyanidin 3-O-rutinoside and cyanidin 3-O-glucoside as the predominant anthocyanins [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, experiments in rats revealed that a diet supplemented with 2% Açai pulp for six weeks caused a reduction in erythrocyte protein oxidation compared to control animals [ 57 ]. In fact, compared with other antioxidant-rich fruits, Açaì extract has 4.8, 6.1, and 7.5-fold the antioxidant capacity of blackberries, blueberries, and strawberries, respectively [ 23 ]. The antioxidant effect of Açaì extract has been attributed to its phytochemical composition comprising hydroxybenzoic acids and flavanols, along with cyanidin 3-O-rutinoside and cyanidin 3-O-glucoside as the predominant anthocyanins [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Functional foods and natural products with antioxidant properties can potentially improve the life functions of erythrocytes and, consequently, the homeostasis of the whole body. Euterpe oleracea, an Amazonian Brazilian fruit popularly known as Açaì [ 23 ], presents several bioactive molecules with different properties, including antioxidant, anti-inflammatory, and analgesic activities, and also modulates calcium homeostasis. The biological effects of Açaì are related to its chemical matrix, which includes numerous phytochemicals components, such as flavonoids [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Increasingly, researchers have focused on natural antioxidants and their capacity to neutralize oxidative stress-induced pathological conditions. Indeed, phytochemical-rich dietary supplementation was found to provide several health benefits [ 25 , 43 , 44 ] and, in this regard, Açai berry represents a good candidate showing different beneficial activities, such as antioxidant properties in various experimental models (in vitro and ex vivo) [ 60 , 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides the intracellular mechanisms, much consideration has been addressed at the antioxidant role of some molecules supplied by the diet [ 43 ]. Euterpe oleracea (known as Açaì) is a typical Amazonian Brazilian fruit [ 44 , 45 , 46 , 47 ] that displays different bioactive compounds with several properties, for example antioxidant activities. Açaì’s biological effects are due to its chemical composition, which includes several phytochemical compounds such as flavonoids [ 48 ], which are able to neutralize ROS and inactivate pro-oxidant molecules [ 49 , 50 ].…”
Section: Introductionmentioning
confidence: 99%
“…Acai is a phytochemical plant with antioxidant, antiinflammatory, and antigenotoxic effects [32][33][34][35][36]. Dried extract of acai berries improves ethanol-induced ulcer in rats [37].…”
Section: Introductionmentioning
confidence: 99%